Analisis Peran Guru Penggerak dalam Mewujudkan Profil Pelajar Pancasila di Sekolah Dasar - Najwa, Lu'luin (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2024)
Abstract: This study aims to analyze the role of Driving Teachers in realizing the Pancasila Student Profile in Elementary Schools (SD). The research method used is qualitative with a case study approach. The results showed that the Driving Teacher has an important role in instilling the values of the Pancasila Student Profile to elementary school students through various strategies, such as leading student-centered learning, becoming learning facilitators, building learning communities, and developing a positive school culture. However, Guru Mobilizer also faces several challenges in carrying out its program, such as lack of support from the school and other stakeholders, limited time and resources, and changes in the mindset of students and teachers. This research contributes to the understanding of the role of Driving Teachers in realizing the Pancasila Student Profile in elementary schools, as well as providing input for Driving Teachers, schools, other stakeholders, and the Ministry of Education and Culture in improving the effectiveness of the Driving Teacher program and realizing the Pancasila Student Profile in elementary schools.Key Words: Teacher Mobilizer, Pancasila Student Profile, Elementary SchoolAbstrak: Penelitian ini bertujuan untuk menganalisis peran Guru Penggerak dalam mewujudkan Profil Pelajar Pancasila di Sekolah Dasar (SD). Metode penelitian yang digunakan adalah kualitatif dengan pendekatan studi kasus. Hasil penelitian menunjukkan bahwa Guru Penggerak memiliki peran penting dalam menanamkan nilai-nilai Profil Pelajar Pancasila kepada peserta didik SD melalui berbagai strategi, seperti memimpin pembelajaran yang berpusat pada murid, menjadi fasilitator pembelajaran, membangun komunitas belajar, dan mengembangkan budaya sekolah yang positif. Namun, Guru Penggerak juga menghadapi beberapa tantangan dalam menjalankan programnya, seperti kurangnya dukungan dari pihak sekolah dan pemangku kepentingan lainnya, keterbatasan waktu dan sumber daya, dan perubahan mindset murid dan guru.Penelitian ini memberikan kontribusi bagi pemahaman tentang peran Guru Penggerak dalam mewujudkan Profil Pelajar Pancasila di SD, serta memberikan masukan bagi Guru Penggerak, pihak sekolah, pemangku kepentingan lainnya, dan Kemendikbudristek dalam meningkatkan efektivitas program Guru Penggerak dan mewujudkan Profil Pelajar Pancasila di SD.Kata Kunci: Guru Penggerak, Profil Pelajar Pancasila, Sekolah Dasar